Evolutionary Relationships Between the Laccase Genes of Polyporales: Orthology-Based Classification of Laccase Isozymes and Functional Insight From Trametes hirsuta - Savinova, Olga S.; Moiseenko, Konstantin V.; Vavilova, Ekaterina A.; Chulkin, Andrey M.; Fedorova, Tatiana V.; Tyazhelova, Tatiana V.; Vasina, Daria V. (Frontiers in Microbiology, 2019)
Laccase is one of the oldest known and intensively studied fungal enzymes capable of oxidizing recalcitrant lignin-resembling phenolic compounds. It is currently well established that fungal genomes almost always contain several non-allelic copies of laccase genes (laccase multigene families); nevertheless, many aspects of laccase multigenicity, for example, their precise biological functions or evolutionary relationships, are mostly unknown. Here, we present a detailed evolutionary analysis of the sensu stricto laccase genes (CAZy – AA1_1) from fungi of the Polyporales order. The conducted analysis provides a better understanding of the Polyporales laccase multigenicity and allows for the systemization of the individual features of different laccase isozymes. In addition, we provide a comparison of the biochemical and catalytic properties of the four laccase isozymes from Trametes hirsuta and suggest their functional diversification within the multigene family.